Control of a five-phase permanent magnet synchronous starter generator for more electric aircraft - Oksuztepe, Eyyup; Yapan, Murat (Gazi Univ, Fac Engineering Architecture, 2024)
The starter generator (SG) system, which is controlled by a single driver, has started to be used in the more environmentally friendly aircraft called More Electric Aircraft, instead of two different systems as starter and generator, which are complex, heavy, and require continuous maintenance, used in traditional aircraft. In this study, a five-phase Permanent Magnet Synchronous Machine (SMSM) was used as SG due to its fault tolerance and higher energy density compared to three-phase, and low weight and volume for the samepower. The SG driver controlled by five phase space vector PWM, the SG controller that manages the wholeprocess, and the aircraft jet engine are modelled in Matlab / Simscape Tollbox. The entire aircraft SG system was controlled in three operating modes: Starter Mode, Transition Mode and Generator Mode. In the proposed system, a more advantageous 270V high voltage DC power system is used compared to the ACpower system in aircraft. According to the aircraft electrical power system standard MIL-STD-704F, for the 270V high voltage DC power system, the maximum steady-state voltage fluctuation is +/- 6V, while the voltage fluctuation is +/- 1V with the proposed system. According to the same standard, the transient fall time from 350V to 270V is requested to be 0.02s and from 200V to 270V rise time to be 0.03s, while in the proposed method these times are 0.017s and 0.015s, respectively. The simulation results showed that the proposed SG system can be used as an aircraft electrical power system.
Elektrik gücünün daha yaygın kullanıldığı uçaklar için beş fazlı sabit mıknatıslı senkron starter generatörün kontrolü
Keywords: Permanent magnet machine; multi-phase systems; starter generator; MEA; space vector PWM